Identification of Rent Relations Results in the Accounting System - Serhiy Bardash; Tetyana Osadcha (Облік і фінанси, 2020)
In the context of the implementation of the concept of sustainable development of individual countries of the post-Soviet space, the study of the problems of accounting for the results of rent relations becomes relevant given the solution of a number of strategic tasks facing businesses today. It is offered to solve the specified problem on the basis of definition in system of concepts of accounting of the economic nature of results of rent relations arising as a result of involvement in economic process of rent-forming factors. The purpose of the article is to formulate proposals for accounting for the results of rental relationships. The methodological basis of the research is the historical and logical method, which is used to study the evolution of rent and approaches to the disclosure of its economic content. The dialectical method and comparative analysis are used to identify significant differences in the definition of rent, formed at different stages and forms of economic relations. Methods of analysis, synthesis, induction, deduction, abstraction, idealization and generalization are used to identify the results of rent relations in the system of accounting concepts and formulate proposals for rent accounting and rent payments. Based on a critical assessment of a certain pluralism of researchers' opinions on the disclosure of the economic content of rent, it is established that: rent is a component of value added, but value added is not taken into account in the accounting system; rent is a component of income from operating activities carried out with the use or exploitation of limited natural resources; the complication of the preliminary valuation of rent makes it impossible to reflect it in income; the amount of rent depends on the demand for the product. Given the above, rent as income from the extraction / use of natural resources, as well as the use of other rent-forming factors, it is proposed to reflect on the off-balance sheet account “Rent” with the allocation of sub-accounts by type of economic rent. It is proposed to attribute rent payments to operating costs, as their inclusion in production costs contradicts the economic nature of such costs, unreasonably increases the cost and contradicts the principle of fair distribution of rent. The practical significance of the study is to increase the level of information disclosure for management decisions, in particular: determining the maximum allowable reduction in the selling price of finished products while maintaining an acceptable level of profitability to increase demand, expand market and, consequently, increase profits; directing all or part of the rent to the implementation of environmental measures, modernization of material and technical base, intensification of innovation.